At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
f-¹(x) = (4- x)/ 3
Step-by-step explanation:
inverse of a function is nothing but the value of x in terms of f(x)
like
if we write f(x) as y we'd get
y = - 3x + 5
so, ill express x in terms of y:-
y= -3x + 4
- adding 3x on both sides of the equation
y + 3x = -3x + 3x + 4
- subtracting y on both sides
y - y + 3x = 4 - y
3x = 4 - y
- dividing the whole equation by 3
x = (4 - y)/ 3
soo, the inverse of the function is x = (4- y)/ 3
mostly we write the inverse in terms of x, hey! don't get confused, when i say this, I simply mean that we're gonna replace y with x and x with f-¹(x).
therefore,
f-¹(x) = (4- x)/ 3
Answer:
[tex]f^{-1} (x)[/tex] = [tex]\frac{-x}{3} + \frac{5}{3}[/tex]
Step-by-step explanation
y = -3x +5 ---> x = -3y + 5 -> y = [tex]\frac{x - 5}{-3}[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.